The Migrant Border Crossing Study: A methodological overview of research along the Sonora–Arizona border. (4th May 2017) - Martínez, Daniel E.; Slack, Jeremy; Beyerlein, Kraig; Vandervoet, Prescott; Klingman, Kristin; Molina, Paola; Manning, Shiras; Burham, Melissa; Walzak, Kylie; Valencia, Kristen; Gamboa, Lorenzo
Abstract : Increased border enforcement efforts have redistributed unauthorized Mexican migration to the United States (US) away from traditional points of crossing, such as San Diego and El Paso, and into more remote areas along the US–Mexico border, including southern Arizona. Yet relatively little quantitative scholarly work exists examining Mexican migrants' crossing, apprehension, and repatriation experiences in southern Arizona. We contend that if scholars truly want to understand the experiences of unauthorized migrants in transit, such migrants should be interviewed either at the border after being removed from the US, or during their trajectories across the border, or both. This paper provides a methodological overview of the Migrant Border Crossing Study (MBCS), a unique data source on Mexican migrants who attempted an unauthorized crossing along the Sonora–Arizona border, were apprehended, and repatriated to Nogales, Sonora in 2007–09. We also discuss substantive and theoretical contributions of the MBCS.